(untitled) (The Proceedings of The International Conference on Climate Change, 2023)
Climate risks, such as floods and droughts, pose a threat to farmers as their livelihood relies on their crop yields. The purpose of this research is to evaluate cash crop and high-value crop farmers’ risk perception towards climate risks, as well as their ability to cope and deal with these risks in Ayutthaya and Chanthaburi Province, Thailand. This study hypothesized that different crop types, farming regions, and socio-economic factors, may play a role in differing risk perceptions in the two groups of farmers. A sample of 100 farmers were chosen from each province via a cluster and purposive sampling technique. Quantitative analysis was used to collect primary data using questionnaires for each group. The findings showed age of durian farmers being younger, with 35% under the age of 30 and 65% of rice farmers 50 or older. Education levels varied greatly as 83% of rice farmers’ highest education completed secondary school, while 38% of durian farmers obtained a bachelor’s degree or higher. Over 50% of each group’s annual household income was under 100,000 baht ( 3,000 USD), with 10% more durian farmers making over 400,000 baht ( 11,000 USD). Data showed that both groups perceive floods and droughts as major risks. According to the survey results, high knowledge and dread level of climate risks were indicated. Regression analysis results determined age and education statistically significant as factors determining risk perception. This study can provide policymakers, agricultural organizations, and future researchers to be able to implement the most effective strategies to protect the farmer, such as infrastructure grants, crop insurance protection plans, and disaster response education.